Analysis of Influencing Factors of Marine Ecological Environmental Governance Capacity - SHEN Shiyi; PENG Bo (Haiyang Kaifa yu guanli)
Based on questionnaire survey data from county and district governments, marine enterprises, non-profit organizations, and the public in Zhoushan City, Zhejiang Province. Using structural equation modeling, it examines the relationship between the four factors of marine ecological environment governance capacity, including comprehensive decision-making intensity, policy implementation strength, regional coordination efficiency, social co-governance level, and the status of marine ecological environment. Research has shown that there is a significant positive relationship between the comprehensive decision-making intensity and policy implementation strength of marine ecological environment governance and the condition of marine ecological environment; Lack of significant direct positive correlation between the effectiveness of regional coordination, the level of social co-governance and marine ecological environment status; There is a significant positive relationship between intensity of comprehensive decision-making and policy implementation, the effectiveness of regional coordination and the level of social co-governance; Regional coordination efficiency plays a significant mediating role between comprehensive decision-making intensity, policy implementation intensity and marine ecological environment status; The level of social co-governance has no significant mediating effect between comprehensive decision-making intensity, policy implementation intensity and marine ecological environment status. Based on this, in order to improve the governance capacity of China's marine ecological environment, the government needs to formulate detailed marine ecological environment protection plans, improve various regulatory indicators, strengthen the coordination and governance of relevant management departments in the same region, as well as cross regional linkage governance, and ensure the corresponding countermeasures and suggestions of the public and non-governmental organizations to know, participate, and supervise the protection of the marine environment.